The Active and Periactive Zone Organization and the Functional Properties of Small and Large Synapses - Cano, Raquel; Tabares, Lucia (Frontiers in Synaptic Neuroscience, 2016)
The arrival of an action potential (AP) at a synaptic terminal elicits highly synchronized quanta release. Repetitive APs produce successive synaptic vesicle (SV) fusions that require management of spent synaptic vesicle components in the presynaptic membrane with minimum disturbance of the secretory apparatus. To this end, the synaptic machinery is structured accordingly to the strength and the range of frequencies at which each particular synapse operates. This results in variations in the number and dimension of Active Zones (AZs), amount and distribution of SVs, and, probably, in the primary endocytic mechanisms they use. Understanding better how these structural differences determine the functional response in each case has been a matter of long-term interest. Here we review the structural and functional properties of three distinct types of synapses: the neuromuscular junction (NMJ; a giant, highly reliable synapse that must exocytose a large number of quanta with each stimulus to guarantee excitation of the postsynaptic cell), the hippocampal excitatory small synapse (which most often has a single release site and a relatively small pool of vesicles), and the cerebellar mossy fiber-granule cell synapse (which possesses hundreds of release sites and is able to translocate, dock and prime vesicles at high speed). We will focus on how the release apparatus is organized in each case, the relative amount of vesicular membrane that needs to be accommodated within the periAZ upon stimulation, the different mechanisms for retrieving the excess of membrane and, finally, how these factors may influence the functioning of the release sites.